RANCANG BANGUN PLATFORM PEMASARAN KONSER VIRTUAL DAN MERCHANDISE DENGAN TEKNOLOGI METAVERSE DAN NFT MENGGUNAKAN METODE SCRUM - Putri Benedicta Simanjuntak (2023)
The COVID-19 pandemic has had a significant negative impact on the music industry as a result of cancellations of concerts and live music due to the government's physical distancing policy. In fact, live concerts are one of the biggest income sources in the music industry. To face this challenge, several musicians have taken steps by holding virtual concerts. In responding to this opportunity, Merchnesia is here to collaborate with Indonesian bands to present a metaverse-based virtual concert experience presented by Telkom's Digital Business Directorate. In addition, Merchnesia comes with a merchandising solution that provides NFT-based physical collectibles that can be connected to the metaverse so that fans can use them both in the real world and in their virtual concert metaverse. To assist Merchnesia in marketing virtual concerts and their merchandise, a marketing platform is needed to assist Merchnesia in conveying information about the band, virtual concert mechanisms and schedules, and official merchandise from the band. The development of this system uses the Scrum method as a method of analysis and system design starting from UML depiction including use case diagrams, activity diagrams, sequence diagrams and class diagrams, application coding, and testing. This research will be conducted for 5 months. The result of this research is a website-based virtual concert and merchandise marketing platform.